Shape Memory Polymer Foams Synthesized Using Glycerol and Hexanetriol for Enhanced Degradation Resistance - Hasan, Sayyeda Marziya (Polymers (Basel), 2020)
Shape memory polymer foams have been used in a wide range of medical applications, including, but not limited to, vessel occlusion and aneurysm treatment. This unique polymer system has been proven to shape-fill a void, which makes it useful for occlusion applications. While the shape memory polymer foam has superior performance and healing outcomes compared to its leading competitors, some device applications may benefit from longer material degradation times, or degradation-resistant formulations with increased fibrous encapsulation. In this study, biostable shape memory polymer foams were synthesized, and their physical and chemical properties were characterized as an initial evaluation of feasibility for vascular occlusion applications. After characterizing their shape memory behavior in an aqueous environment, degradation of this polymer system was studied in vitro using accelerated oxidative and hydrolytic solutions. Results indicated that the foams did not lose mass under oxidative or hydrolytic conditions, and they maintained high shape recovery in aqueous in vitro models. These degradation-resistant systems have potential for use in vascular occlusion and other wound healing applications that benefit from permanent, space-filling shape memory behavior.